ABOUT ARCHAEOLOGICAL RESEARCH AT THE KUVA MONUMENT (UBS Scientific Bulletin, 2024)
In this article, located at the crossroads of the Great Silk Road, which played a special role in the history of the intercontinental communication route from Kunchikar to Kunbotar, unlike other cities of the Fergana Valley, a lot of ancient cultural layers are well preserved. A brief description of the archaeological research carried out at the Couva monument is given.